Mauryius n.gen. (Scorpiones: Bothriuridae), a new neotropical scorpion genus - Ojanguren Affilastro, Andres Alejandro (2017)
Mauryius, n.gen., a new bothriurid scorpion genus from the Argentinean Precordillera, is described, and its phylogenetic position is discussed based on a phylogenetic analysis of morphological data. Mauryius, n.gen. is the first scorpion genus endemic to the Argentinean Precordillera. It is most closely related to Pachakutej Ochoa, 2004 from the inter-Andean valleys of Peru and to Rumikiru Ojanguren-Affilastro, Mattoni, Ochoa & Prendini, 2012 from the Atacama Desert in Chile. Mauryius cuyanus, n.sp., the only known species of the genus, is described. Biogeographical implications of Mauryius relationships are discussed.